REACTION OF FOREST FLOOR ORGANIC MATTER AT GOETHITE, BIRNESSITE AND SMECTITE SURFACES - Chorover J.; Amistadi M.K. (My University, 2001)
Experiments were conducted to compare the affinity and reactivity of three different minerals for natural organic matter (NOM) in forest floor leachate (FFL) from hardwood and pine forests. The FFLs were acidic (pH 4) with ionic strengths of 1.4 mM (hardwood) and 1.1 mM (pine), and they contained larger organic molecules (weight average molecular weights [Mw] = 5-6 kDa) than has been reported recently for surface waters using similar methods. A synthetic diluent solution was prepared to match the inorganic chemistry of the FFL and to provide a range of initial dissolved organic carbon (DOC) concentrations (0-140 g C m-3) for reaction with goethite (α-FeOOH), birnessite (δ-MnO2) and smectite (montmorillonite, SWy-2) in suspension, and in corresponding blanks.A variety of macroscopic and spectroscopic methods were employed to show that reaction with the three minerals resulted in distinctly different NOM adsorption, fractionation and transformation patterns. Goethite exhibited a steep initial slope in the adsorption isotherm and a maximum retention of 10.5 g C kg-1. The isotherm for montmorillonite was more linear, but equal amounts of C were adsorbed to goethite and montmorillonite (per unit sorbent mass) at maximum DOC. Whereas preferential uptake of high Mw, aromatic constituents via ligand exchange was observed for goethite, compounds of lower than average Mw were retained on montmorillonite and no preference for aromatic moieties was observed. Birnessite, which has an isoelectric point of pH < 2, retained low amounts of organic C (<2 g c kg-1) but exhibited the highest propensity for oxidative transformation of the NOM. The data indicate that fractionation behavior of NOM is dependent on mineral surface chemistry in addition to sorbent affinity for organic C. This work also emphasizes the fact that abiotic transformation reactions must be considered in studies of NOM interaction with Fe(III) and Mn(IV) containing solid phases.